The Implementation of Think – Pair – Share Technique to Improve Students’ Ability in Speaking English at Tenth Grade of Senior High School 1 Jember - Annisa, Nur; Arifiatun, Arifiatun; Mufaridah, Fitrotul (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2024)
Communication is necessary in human life. Therefore, language is being very important to be learnt or even to be mastered by people. As better language people has as better the other people understand about the purpose. Discussing a language, English is common-known as the universal language in this world. This research was aimed to find out the implementation of Think – Pair – Share Technique in teaching speaking skill. This research was conducted by using Classroom Action Research. The subject of the research was the tenth grade students of SMAN 1 Jember in academic year 2022/2023 which consisted of 36 students. The objective of this research was to find out the improvement of students’ speaking skill through the implementation of Think – Pair – Share Technique. This research was conducted in two cycles which each consists of planning, acting, observing, and reflecting. The data were gathered through quantitative and qualitative data. The result of the research showed that there was an increasing of students’ speaking skill. It can be proven by the enhancement of students’ fluency, pronunciation and courage in speaking. Based on that data, the think – pair – share technique was successfully way to improve students’ ability in speaking. Students’ score was significantly increased.